Prevalence of Hypocalcemia in Term Neonates with Moderate to Severe Birth Asphyxia in a Tertiary Care Hospital, Lahore - Atiqa; Shahzad, Qamar Uz Zaman; Arif Malik, Muhammad Ahmed; Siddique, Hira; Mukhtar, Nida; Amanat, Maria (Indus Journal of Bioscience Research, 2025)
Background: Birth asphyxia is a significant cause of neonatal morbidity and mortality. Hypocalcemia is a common metabolic complication in neonates with birth asphyxia, which may lead to severe consequences such as seizures and poor feeding. Objective: To assess the prevalence of hypocalcemia in term neonates with moderate to severe birth asphyxia and evaluate the associations between hypocalcemia and demographic/clinical variables. Methods: This cross-sectional study was conducted at the Neonatal Unit of the Department of Pediatric Medicine, Shalamar Hospital, Lahore, from 15 April 2024 to 15 October 2024. A total of 178 neonates with birth asphyxia were enrolled using a non-probability consecutive sampling technique. Data were collected on demographic characteristics, APGAR scores, serum calcium levels, and birth weight. Hypocalcemia was defined as serum calcium levels